2023
DOI: 10.1021/acs.jpcb.3c03799
|View full text |Cite
|
Sign up to set email alerts
|

Using Implicit-Solvent Potentials to Extract Water Contributions to Enthalpy–Entropy Compensation in Biomolecular Associations

Abstract: Biomolecular assembly typically exhibits enthalpy−entropy compensation (EEC) behavior whose molecular origin remains a long-standing puzzle. While water restructuring is believed to play an important role in EEC, its contribution to the entropy and enthalpy changes, and how these changes relate to EEC, remains poorly understood. Here, we show that water reorganization entropy/enthalpy can be obtained by exploiting the temperature dependence in effective, implicit-solvent potentials. We find that the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…The plot shows the kind of behavior usually denoted as an enthalpy-entropy compensation (EEC). This type of behavior has been repeatedly reported for more than fifty years in many experiments closely associated with protein-ligand interactions in water solution [6][7][8]10,[31][32][33][34][35][36]. As can be observed in part B of the same figure, it is accompanied by the lack of correlation of ∆H • vs. ∆G • , which is, in turn, usually found in chemical transformations, mostly in gaseous phase, and having a simple stoichiometry similar to that of a simple protein-ligand interaction.…”
Section: Protein-ligand Interactionssupporting
confidence: 62%
See 2 more Smart Citations
“…The plot shows the kind of behavior usually denoted as an enthalpy-entropy compensation (EEC). This type of behavior has been repeatedly reported for more than fifty years in many experiments closely associated with protein-ligand interactions in water solution [6][7][8]10,[31][32][33][34][35][36]. As can be observed in part B of the same figure, it is accompanied by the lack of correlation of ∆H • vs. ∆G • , which is, in turn, usually found in chemical transformations, mostly in gaseous phase, and having a simple stoichiometry similar to that of a simple protein-ligand interaction.…”
Section: Protein-ligand Interactionssupporting
confidence: 62%
“…A linear enthalpy-entropy relationship is frequently associated with thermodynamic protein-ligand interactions [1][2][3][4][5][6][7][8]. When the reaction enthalpy values, ∆H • , associated with any particular set of ligand-protein interactions are plotted against the corresponding changes in entropy values, T∆S • , a straight line with a slope close to 1 is usually obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any entropic changes due to solvent reorganization resulting from the bond are separate mechanisms that need to be understood. Recent MD simulations have shown that the reorganization of water drives the association of charged and uncharged polymers, and this reorganization is also suggested as the main driving force for molecular recognition …”
Section: Introductionmentioning
confidence: 99%
“…These electronic environment changes or amine-catalyzed ester hydrolysis (as has been proposed for other amine and ester containing polymers) may underlie differences in polymer behavior as a function of charge state. Likely, some combination of these factors, local pH changes, , counterion condensation, , water organization changes, local dielectric changes, electron distribution, and/or amine-catalyzed hydrolysis, results in the faster degradation of PBAEs relative to their charged, quaternary analogs.…”
mentioning
confidence: 99%